2021
DOI: 10.5194/gmd-14-4573-2021
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm modelling in the global land surface model ORCHIDEE-MICT

Abstract: Abstract. Oil palm is the most productive oil crop that provides ∼ 40 % of the global vegetable oil supply, with 7 % of the cultivated land devoted to oil plants. The rapid expansion of oil palm cultivation is seen as one of the major causes for deforestation emissions and threatens the conservation of rain forest and swamp areas and their associated ecosystem services in tropical areas. Given the importance of oil palm in oil production and its adverse environmental consequences, it is important to understand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Meanwhile, we also found that the age of OP stands influences LAI, as the LAI of OP increases stand age when OP is young, and then decrease LAI after a threshold of stand age. This observation agrees with previous studies reporting the plateau and decreases of oil palm LAI after the age of 10 (Xu et al, 2021), and the plateau and decrease of oil palm yield after age of 8-9 (Park et al, 2023). The stand age of most OP planted in Southeast Asia is approaching maturity (over half are planted before 2009) (Danylo et al, 2021).…”
Section: Minor Contribution Of Oil Palm To Regional Greennesssupporting
confidence: 92%
“…Meanwhile, we also found that the age of OP stands influences LAI, as the LAI of OP increases stand age when OP is young, and then decrease LAI after a threshold of stand age. This observation agrees with previous studies reporting the plateau and decreases of oil palm LAI after the age of 10 (Xu et al, 2021), and the plateau and decrease of oil palm yield after age of 8-9 (Park et al, 2023). The stand age of most OP planted in Southeast Asia is approaching maturity (over half are planted before 2009) (Danylo et al, 2021).…”
Section: Minor Contribution Of Oil Palm To Regional Greennesssupporting
confidence: 92%
“…LSMs simulate plant growth, biomass density, crop yields, and fluxes of energy, nutrients, water and carbon, which are used to make projections of global climate impacts. While the importance of adequately representing oil palm as a distinct plant functional type (PFT) within LSMs is beginning to be recognized, models that incorporate this difference are often calibrated with data from a few plantations in Malaysia and Indonesia (Xu et al, 2021), highlighting the importance of knowing whether oil palm plantations in Mexico, and more generally Latin America, follow different behaviors than those in Southeast Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Complementando al anterior análisis, el desarrollo vegetativo y productivo de la palma aceitera (Figura 3), toma al menos 10 años para que sus rendimientos sean los máximos, manteniendo esta capacidad hasta los 25 años (Xu et al, 2021). Así, durante los primeros 5 años, la planta prioriza el desarrollo de tallo y follaje, incrementando esta capacidad fotosintética hasta los 10 años (Figura 3.A); desde el quinto año, la producción del fruto empieza a ser importante, estos rendimientos van incrementando gradualmente hasta el décimo año, donde alcanza su madurez productiva, momento desde el cual sus rendimientos son los más elevados y con cierta estabilidad en función del tiempo y el clima (Figura 3.B).…”
Section: Análisis De Datosunclassified